2007
DOI: 10.1021/jf070120r
|View full text |Cite
|
Sign up to set email alerts
|

Which Impact for β-Damascenone on Red Wines Aroma?

Abstract: beta-Damascenone, a C-13 norisoprenoid compound, is usually presented as an impact odorant in red wines. Its direct contribution to their aroma was investigated. Both free beta-damascenone and beta-damascenone precursors were isolated from various French red wines and then analyzed by gas chromatography-mass spectrometry, revealing concentrations in the vicinity of 1 and 2 microg/L for free compounds and both forms, respectively. Gas chromatography-olfactometry analyses were also performed on dilutions of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
191
3
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(214 citation statements)
references
References 30 publications
14
191
3
6
Order By: Relevance
“…The combination of analytical and sensory methodologies has been particularly important in resolving effects of interactions of aroma compounds with the nonvolatile matrix (Pineau et al 2007, Robinson et al 2009, Sáenz-Navajas et al 2010) as well as with other volatile compounds (Atanasova et al 2005, Escudero et al 2007, Pineau et al 2009). These interactions may result in variations in the sensory character of the mixture due to perceptual enhancement and suppression effects as well as to physicochemical effects on volatility and release of the aroma compounds.…”
Section: Origins Of Wine Aromamentioning
confidence: 99%
“…The combination of analytical and sensory methodologies has been particularly important in resolving effects of interactions of aroma compounds with the nonvolatile matrix (Pineau et al 2007, Robinson et al 2009, Sáenz-Navajas et al 2010) as well as with other volatile compounds (Atanasova et al 2005, Escudero et al 2007, Pineau et al 2009). These interactions may result in variations in the sensory character of the mixture due to perceptual enhancement and suppression effects as well as to physicochemical effects on volatility and release of the aroma compounds.…”
Section: Origins Of Wine Aromamentioning
confidence: 99%
“…This can be attributed to the fact that GC-O analysis essentially evaluates the aroma of the compounds individually and separate from the sample matrix. GC-O does not take into account the interaction effects that occur when aroma compound interact with the nonvolatile matrix (Pineau et al 2007, Robinson et al 2009, Sáenz-Navajas et al 2010, 2012 and with other volatile compounds (Atanasova et al 2005b, Escudero et al 2007, Pineau et al 2009). As discussed later, these interactions may result in variations in the sensory character of the mixture due to enhancement and suppression effects.…”
Section: Gc-olfactometrymentioning
confidence: 99%
“…For example, using descriptive analysis, it has been shown that fruity aromas in wines can significantly mask vegetal characters in the wines (Hein et al 2009). Similarly, at low concentrations, β-damascenone has the ability to mask the herbaceous aroma associated with 3-isobutyl-2-methoxypyrazine (Pineau et al 2007) while enhancing the berry fruit aromas in red wines (Escudero et al 2007, Pineau et al 2007). As noted in the above section, the aromas of wine blends exhibited suppressive and amplifying effects when the intensity of specific aroma attributes of the blends was compared to the original aroma of the monovarietal wines (Hopfer et al 2012a).…”
Section: Sensory Evaluation Of Winementioning
confidence: 99%
See 1 more Smart Citation
“…Floral and exotic fruit notes are attributed to -damascenone, and due to its low odour threshold it can have a great sensorial impact on wines (Guth, 1997). However, other authors attribute its importance to a potentiating role of the fruit aromas of other compounds, rather than -damascenone acting alone (Pineau et al, 2007).…”
Section: Varietal Aroma Compoundsmentioning
confidence: 99%